Pemanfaatan Ekstrak Hipotalamus Kambing Sebagai Upaya Optimalisasi Kesuburan Kambing Kejobong Betina (THE USE OF GOAT HYPOTHALAMIC EXTRACT TO OPTIMALIZE FERTILITY OF FEMALE KEJOBONG GOATS) - ., Zulkarnain; ., Sutiyono; Setiatin, Enny Tantini (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
The objective of this study was to investigate the effect of hypothalamic extracts level on quality levelof estrous, pregnancy percentage and litter size of Kejobong goats. The materials used in this experimentwere the hypothalamus glands and 23 female Kejobong goats aged between 3-4 years. The experimentaldesign used in this study was a completely randomized design with 3 treatments 7-8 replicates. Thetreatment groups used in this study were T0 injected with 5 mL of 0.9% physiologic saline, T1 injected witha solution consisted of 2 mL of hypothalamic extract added 3 mL of 0.9% physiologic saline, T2 injectedwith solution consisted of 4 mL of hypothalamic extract added 1 mL of 0.9%physiologic saline. Theparameters were the percentage of estrous, estrous quality, onset of estrous, estrous length, pregnancypercentage and litter size. The data were analyzed by using analysis of variance and Chi-square. Theresults showed that hypothalamic extract was highly significant (P <0.01) affected the estrous length andhad no effect (P> 0.05) on the other parameters. In conclusion hypothalamic extracts may optimize thefertility of female Kejobong goats evaluated from estrous length, pregnancy percentage and litter size.
Keywords: hypothalamic extract, estrous, fertility, pregnancy, Kejobong goats